Stunting and Quality of Life: The nexus between Malnutrition, Community Empowerment and Economic Development - Danapriatna, Nana; Ramadhan, M Fakhran; Putra, Purnama; Zhafiraah, Nazma Riska (Entrepreneurship and Community Development, 2023)
The community service program was implemented to overcome the stunting problem in Lenggahsari Village, Bekasi Regency, West Java. Stunting due to malnutrition causes pollution to become a problem in this village. The government has taken serious steps with the national stunting prevention movement. The method used is socialization and training about stunting, which aims to change mindsets towards a clean and healthy environment, support zero new stunting, and improve the quality of life. The flow stages of implementing this service program include preparation, stunting socialization, and evaluation. The results of implementing the community service program are increasing knowledge and changing the local community's mindset regarding the dangers of stunting and reducing the stunting rate in Lenggahsari Village. The socialization of stunting prevention is a step in contributing to the government and the state in the economic growth and development of the country; stunting prevention is a long-term investment in the next generation.